Not All Posttraumatic Stress Disorder Symptoms Are Equal: Fear, Dysphoria, and Risk of Developing Hypertension in Trauma-Exposed Women - Sumner, Jennifer A. (Psychol Med, 2019)
BACKGROUND: Posttraumatic stress disorder (PTSD) is associated with higher risk of incident hypertension, but it is unclear whether specific aspects of PTSD are particularly cardiotoxic. PTSD is a heterogeneous disorder, comprising dimensions of fear and dysphoria. Because elevated fear after trauma may promote autonomic nervous system dysregulation, we hypothesized fear would predict hypertension onset, and associations with hypertension would be stronger with fear than dysphoria. METHODS: We examined fear and dysphoria symptom dimensions in relation to incident hypertension over 24 years in 2,709 trauma-exposed women in the Nurses’ Health Study II. Posttraumatic fear and dysphoria symptom scores were derived from a PTSD diagnostic interview. We used proportional hazards models to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for each symptom dimension (quintiles) with new-onset hypertension events (N=925), using separate models. We also considered lower-order symptom dimensions of fear and dysphoria. RESULTS: Higher levels of fear (P-trend=.02), but not dysphoria (P-trend=.22), symptoms were significantly associated with increased hypertension risk after adjusting for socio-demographics and family history of hypertension. Women in the highest versus lowest fear quintile had a 26% higher rate of developing hypertension [HR=1.26 (95% CI,1.02–1.57)]; the increased incidence associated with greater fear was similar when further adjusted for biomedical and health behavior covariates (P-trend=.04) and dysphoria symptoms (P-trend=.04). Lower-order symptom dimension analyses provided preliminary evidence that the re-experiencing and avoidance components of fear were particularly associated with hypertension. CONCLUSIONS: Fear symptoms associated with PTSD may be a critical driver of elevated cardiovascular risk in trauma-exposed individuals.